ALGORITHMS FOR THREE-POINT LIGHTING ADJUSTING FOR MONITORING OR STAGE OBJECTS CAPTURE: ALGORITHMS FOR THREE-POINT LIGHTING ADJUSTING FOR MONITORING OR STAGE OBJECTS CAPTURE - Dzhurov , Kaloyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Every scene in the filming has requirements for lighting. Standard lighting could use a three-point scheme of light sources. Highlighting the object on the background could easily be achieved if these sources are adjusted automatically by certain algorithms. There is two algorithm with three-point adjustment of light sources simulation in MATLAB.